Prediction of the extremal shape factor of spheroidal particles - Hlubinka, Daniel (Image analysis and stereology, 2001)
In the stereological unfolding problem for spheroidal particles the extremal shape factor is predicted. The theory of extreme values has been used to show that extremes of the planar shape factor of particle sections tend to the samelimit distribution as extremes of the original shape factor for both the conditional and marginal distribution. Attention is then paid to the extreme shape factor conditioned by the particle size. Normalizing constants are evaluated for a parametric model and the numerical procedure is tested on realdata from metallography.
Keywords: Particle Size; Aluminijeve spojine; Delec, velikost; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Aluminum Compounds; Modeli statistični; Models, Statistical; statistični modeli; stereologija